Pendampingan Pemanfaaatan Media Sosial sebagai Sarana Membangun Citra Pondok Pesantren Nurul Mustafa Al-Husaini - Andi Yusika Rangan; Siti Qomariah; Amelia Yusnita (BANTENESE : JURNAL PENGABDIAN MASYARAKAT, 2021)
Public relations (public relations) are one of the processes in building the image of an institution. Social media has emerged as a flexible and informative means of communication. Social media is one of them because of features such as sharing text or writing, photos and videos. with assistance carried out in terms of making social media, processing content and publishing content on facebook, instagram and youtube, boarding school administrators can interact with the wider community, improve the image of the institution despite the limited human resources and funding with the right digital branding strategy.